A Second Trimester Caesarean Scar Pregnancy. (23rd March 2014) - Sikka, Pooja; Suri, Vanita; Chopra, Seema; Aggarwal, Neelam
Abstract : Caesarean scar pregnancy, where conceptus is implanted on previous scar, is a rare entity. We present one such case of scar pregnancy presenting to us in the second trimester and was managed with methotrexate and uterine artery embolization, followed by hysterotomy. Uterus could be conserved and hysterectomy could be avoided.